Cobalt‐Nanoporous Carbon Functionalized Nanocomposite‐Based Triboelectric Nanogenerator for Contactless and Sustainable Self‐Powered Sensor Systems (Adv. Funct. Mater. 52/2021). (22nd December 2021) - Rana, S. M. Sohel; Zahed, Md Abu; Rahman, M. Toyabur; Salauddin, M.; Lee, Sang Hyun; Park, Chani; Maharjan, P.; Bhatta, T.; Shrestha, Kumar; Park, Jae Yeong
Abstract : Self‐Powered Sensor Systems In article number 2105110, Jae Yeong Park and co‐workers develop a metal–organic framework‐based Co‐NPC/Ecoflex nanocomposite and evaluate it as a highly negative layer in a contactless double layer triboelectric nanogenerator (CDL‐TENG). The porous structure of the Co‐NPC provides a large surface area to enhance the charge generating capability and the MXene/Ecoflex nano composite improves the functionality of the CDL‐TENG. The CDL‐TENG exhibits excellent charge trapping capability and is ultra‐flexible, sustainable, and highly sensitive in non‐contact, self‐powered sensor applications.